Struktur dan Komposisi Tumbuhan Bawah di Zona Pegunungan Bawah Blok Malagembol, Cagar Alam Gunung Tilu, Jawa Barat - Tri Cahyanto; Dian Muhamad Ramdan; Salma Salsabila; Muhammad Efendi; Ida Yayu Nurul Hizqiyah (Program Studi Pendidikan Biologi, FKIP Unpas,, 2022)
The understorey is one type of tropical forest vegetation that contributes to the complexity of the forest structure. The habitat of the understorey is closely related to the condition of the vegetation. This study aims to determine the structure and composition of the understorey to support the ecological function and habitat in the Malagembol Block, Mount Tilu Nature Reserve. The sample collection was carried out using the sample plot method. A total of three main plots measuring 10×100 m2 were divided into ten subplots with a size of 5×5 m2. The understorey observed included herbaceous plants and saplings with a height of less than 1 m. The data analysis included the calculation of frequency, density, individual dominance, and significant value index using heterogeneity index (Shannon-Wiener), richness index (Margalef), and evenness index. A total of 186 species and 66 understorey families were recorded in the observation plots. Based on their stature, they were grouped into 26 species of climbing plants, 43 species of herbaceous plants, and 116 species of saplings. The species richness was high and more diverse. In addition, the species found were evenly distributed in each observation plot and the plant community was relatively stable. The Mount Tilu Nature Reserve has an important contribution of understorey plants in compiling the ecosystem so that it becomes a further consideration for the management of the area around Mount Tilu Nature Reserve.